The WHO Reproductive Health Library - Gulmezoglu, A Metin (Geneva : World Health Organization, 2009)
The WHO Reproductive Health Library (RHL) provides up-to-date eviden ce and implementation aids for best practice in sexual and reproductive health care.
The WHO Reproductive Health Library (RHL) is an annual electronic re view journal of the Department of Reproductive Health and Research, Wor ld Health Organization, Geneva, Switzerland.
Produced by the World Health Organization; edited by A.Metin Gulmezo glu
Keywords: Digital libraries; Social service and sex; Reproductive health